How Earnings Management Mediates Disclosure and Board Performance on SOE Quality - Ela Fauziah; Adibah Yahya; Widiastuti Widiastuti; Estuti Fitri Hartini; Catur Okta Salsabila (Politeknik Ganesha Medan, 2026)
This study examines the critical determinants of financial reporting integrity within State-Owned Enterprises (SOEs) by evaluating the relationships between corporate governance mechanisms, earnings management, and earnings quality. Utilizing a quantitative approach with path analysis, this research assesses how external transparency and internal board monitoring affect the quality of reported income, and whether earnings management acts as an intervening behavioral mechanism. The sample size for this study comprises 12 companies, covering the period 2021–2025. The empirical results demonstrate that financial reporting transparency exerts a significant negative influence on earnings management, yet has no direct effect on earnings quality. Meanwhile, board effectiveness does not significantly influence either earnings management or earnings quality. Conversely, a high level of earnings management significantly degrades the overall predictability and sustainability of reported earnings. Crucially, the Sobel test analysis reveals that earnings management does not serve as a significant mediating pathway between corporate governance structures and financial reporting outcomes. This non-mediating dynamic implies that within state-backed institutional environments, robust disclosure mandates and strict supervisory frameworks directly enforce financial reporting excellence through rigid bureaucratic and regulatory compliance rather than relying on an indirect behavioral channel. These findings suggest that government regulators must maintain stringent selection criteria for independent commissioners and enforce comprehensive disclosure protocols as the most reliable direct guardrails for protecting public resources.